2013
DOI: 10.1590/s1516-14392013005000086
|View full text |Cite
|
Sign up to set email alerts
|

Strength and stiffness of thermally rectified eucalyptus wood under compression

Abstract: The aim of this work was the evaluation of the thermal-rectification process of reforestation wood Corymbia citriodora Hook by measuring of mechanical properties under compression parallel to the grain and also determining of chemical composition. The tested samples were thermally treated in a furnace with nitrogen-atmosphere at heating rate of 0.033 °C.min -1 , at temperatures of 160, 180, 200, 220 and 240 °C. The chemical components and mechanical properties were affected with the thermal rectification proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 24 publications
(44 reference statements)
3
18
0
1
Order By: Relevance
“…The MOR results (~12-15MPa) have reached the minimum requirements found in the normative documents. Particleboards made only with eucalyptus wood achieved higher MOE values (up to 47%) than the Brazilian standard requirements (~1.7-2.7 GPa) 30 . Belini et al 19 have investigated particleboard panels reinforced with sugarcane bagasse and eucalyptus fibres impregnated with formaldehyde urea.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The MOR results (~12-15MPa) have reached the minimum requirements found in the normative documents. Particleboards made only with eucalyptus wood achieved higher MOE values (up to 47%) than the Brazilian standard requirements (~1.7-2.7 GPa) 30 . Belini et al 19 have investigated particleboard panels reinforced with sugarcane bagasse and eucalyptus fibres impregnated with formaldehyde urea.…”
Section: Resultsmentioning
confidence: 71%
“…This is the first component to degrade being revealed by the consumption of hydroxyl groups from the water molecules. For this reason, reductions in equilibrium moisture content and thickness swelling have been reported in the literature 15,29,30 . In order to avoid any environment effect mainly on the core material, the peripherical sides of the samples were painted with epoxy polymer.…”
mentioning
confidence: 93%
“…The increase in the proportional lignin content during the heat treatment was caused by degradation of the hemicelluloses and cellulose and the condensation reactions of lignin (Wikberg and Maunu 2004;Tumen et al 2010;Silva et al 2013). In our experiment, an increase in the relative content of lignin was observed at temperatures over 220 °C.…”
Section: Chemical Changesmentioning
confidence: 99%
“…According to Silva et al (2013), the increase in the MOE at lower treatment temperatures can also be caused by an increase in the crystallinity of cellulose and in the relative content of lignin. Beyond the temperature of 220 °C, the MOR of the treated wood was lower than that of the untreated wood.…”
Section: Changes In Mechanical Propertiesmentioning
confidence: 99%
“…The effect of thermal modification on mechanical properties of wood is complex, and the magnitude of this effect is a function of parameters such as exposure time, temperature, medium rate of heating, and the moisture content of wood (Yildiz et al 2006;Korkut and Hiziroglu 2009). The decrease in compression strength was due to the holocellulose content degradation, in which the first constituent affected was probably the hemicellulose (da Silva et al 2013). Nuopponen (2005) found that thermally treated wood specimens showed higher lignin contents than unheated wood specimens, which was the result of the degradation of hemicellulose.…”
Section: Cspg Of Impregnated and Heat-treated Oriental Beechmentioning
confidence: 99%